Ecological agriculture and biodiversity: Relationships, congruences, objective conditions and perceptions of local actors - Violeta Florian; Marioara Rusu; Elisabeta Roşu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
Ecological agriculture provides a favourable framework for maintaining biodiversity by using economically and socially efficient friendly farming practices, generating modern attributes to rural communities and offering a different lifestyle and a different quality of life to the entire society. In two counties ranking in the top ten counties with areas cultivated under organic farming system, Cluj and Suceava, there are positive implications of these farming practices on biological diversity. Qualitative research methods were used to see the local/rural actors' opinion on this topic: hybrid forum and in-depth-interviews. Farmers' decisions to adopt sustainable practices for the environment, which provide positive externalities for biodiversity, water, soil and landscapes, are generated by business-specific economic and social rationality tending to achieve profit specific objectives by using traditional knowledge and skills from the intangible rural heritage.
Keywords: Q15; R11; 330; ecological agriculture; biodiversity; rural communities; local actors